Evaluation of the cost saving potential of introducing Benepali® and Flixabi® on the European and Italian markets - Negrini, Cristina; Psachoulia, Emi (Farmeconomia. Health Economics and Therapeutic Pathways, 2017)
INTRODUCTION: Biosimilar products play an important role in improving the access to biological medicines for an increased number of patients and enhancing the financial sustainability of the health systems.AIM: To assess the cost saving potential associated with the introduction of two biosimilars (Benepali® and Flixabi®) vs. their respective reference biological products on the European and Italian markets.METHODS: A budget impact model was developed to estimate the cost saving of the hypothetical introduction of Benepali® and Flixabi® vs. Enbrel® and Remicade®, respectively, in three European countries. The analysis was conducted from the payer perspective, over a 3-year period. In addition, the same model was used to assess the impact of Benepali® vs. Enbrel® in three Italian regions over a 2-year period. The model compares the costs associated with the current treatment patterns, used to manage patients with all the conditions which Benepali® and Flixabi® are authorized for, with that of a hypothetical treatment pattern in which biosimilar products have been introduced. Only direct costs associated with the drug acquisition were considered. The model was constructed using published country- or region-specific data, where available. Annual drug acquisition costs were calculated using the dosing information from SPCs and country-/region-specific price lists.RESULTS: The introduction of Benepali® and Flixabi® in the biologic therapeutic setting of three European countries resulted in substantial cost savings across the entire scenario, with different penetration over a 3-year period. Similarly, over a 2-year horizon, the introduction of Benepali® in the biologic therapeutic setting of three Italian regions resulted in significant cost savings. In all cases, the greater savings were observed in the scenario where the biosimilars’ penetration was higher.CONCLUSIONS: The introduction of Benepali® and Flixabi® has a substantial cost saving potential for the Italian and European health systems, and the budget impact is sensitive to the uptake rates of the biosimilars market.